Metal‐Free One‐Pot Synthesis of Benzofurans. Issue 29 (20th June 2014) - Ghosh, Raju; Stridfeldt, Elin; Olofsson, Berit
Abstract Ethyl acetohydroxamate was efficiently arylated with diaryliodonium salts at room temperature under transition‐metal‐free conditions. The obtained O‐arylated products were reacted in situ with ketones under acidic conditions to yield substituted benzo[b]furans through oxime formation, [3, 3]‐rearrangement, and cyclization in a fast and operationally simple one‐pot fashion without using excess reagents. Alternatively, the O‐arylated products could be isolated or transformed in situ to aryloxyamines or O‐arylaldoximes. The methodology was applied to the synthesis of Stemofuran A and the formal syntheses of Coumestan, Eupomatenoid 6, and (+)‐machaeriol B.